The effect of slurry preparation methods on biaxial flexural strength of dental porcelain. (2023)
One-step and incremental mixing procedures are currently used to produce dental ceramic pastes. In the ceramic industry, high quality is obtained using one-step mixing, but in dentistry, the best method has not been yet determined.